(untitled) (Fiep Bulletin - online, 2014)
The handgrip strength measurement by hand dynamometer has been used as a way to evaluate the general functionality in healthy or unhealthy individuals of several age ranges. This study had the objective to evaluate the handgrip strength from the sixth decade of life, using hand dynamometry in elders from Cascavel - PR. Volunteers older than 60 years old, from both genders, were selected from a non institutionalized elder condominium and from an elderly home care, that were stratified by age groups (10 years range for each group). The volunteers were evaluated by hand dynamometer realized on a standardized position, and the obtained results demonstrated a decrease on the handgrip strength values when these are compared between the groups of 60 - 69 years and > 80 years, for both men and women, and also smaller rates for those elders that were institutionalized. That way, it was possible to conclude that, on the evaluated volunteers, the handgrip strength presented a decrease related to age, for both men and women, and this decrease was also bigger for those institutionalized.